The Transformation of Madhhab and Theology in Egypt from al-Maqrizi’s Perspective: Epistemological Foundations for the Renewal of Islamic Education - Maulana Ridho, Arman; Jinan, Mutohharun (IJBLE Scientific Publications Community Inc., 2026)
This study examines the transformation of madhhab and theology in Egypt as documented in al-Maqrizi’s Madhāhib Ahl Miṣr wa ‘Aqā’idihim and analyzes its relevance as an epistemological foundation for the renewal of contemporary Islamic education. Employing a qualitative approach with historical methods and historical hermeneutics, the research analyzes classical texts alongside contemporary academic literature and Islamic education policy documents. The findings reveal three interrelated patterns: the dynamic transformation of legal schools and theology shaped by political power and educational institutions; the strong connection between socio-political change, scholarly mobility, and educational orientation; and the epistemological continuity between classical theological rationality—particularly Ash‘arism—and modern Islamic educational reform. These patterns demonstrate that Islamic education in Egypt has historically developed through adaptive mechanisms rooted in internal intellectual traditions rather than through abrupt or externally imposed change. The study concludes that al-Maqrizi’s work should be understood not merely as a historical record but as a living epistemological resource that informs contemporary debates on Islamic education reform. By emphasizing historical continuity between classical scholarship and modern institutional change, this research contributes to a more historically grounded and integrative understanding of Islamic education, with implications for both Egyptian and Indonesian contexts.